تقييم كتب التربية الإسلامية للمرحلة الأساسية المتوسطة في الأردن في ضوء المعايير المعاصرة للتربية البيئية - أبو غليون، عيد إسماعيل عبد ربه Abu Ghalion, Eid Ismail Abd Rabbuh (المركز القومي للبحوث بغزة, 2016)
هدفت هذه الدّراسة إلى تقييم كُتب التّربية الإسلامية للمرحلة الأساسية المتوسطة في الأردن في ضوء المعايير المعاصرة للتّربية البيئية. تكوّنت عينة الدّراسة من مجتمع الدّراسة نفسه، وهي كُتب التّربية الإسلامية للمرحلة الأساسية المتوسطة الصادرة عن وزارة التّربية والتعليم للعام الدّراسي 2015/2016. وتحقيقاً لأهداف الدّراسة، قام الباحث ببناء قائمة بمعايير التّربية البيئية المعاصرة ومن ثَمَّ تم تطويرها إلى أداة لتحليل الكتب المذكورة. اشتملت أداة الدراسة على تسعة محاور تضمنت سبعة وعشرين معياراً معاصراً للتّربية البيئية، وقد تمّ عرض الأداة على لجنة من المحكمين المتخصّصين في المناهج والبيئة؛ للتأكد من صدقها، ثمّ قام الباحث بعملية التحليل حيث تمّ تكليف أحد المعلمين، ويحمل درجة البكالوريوس في المناهج وطرق تدريس التّربية الإسلامية للقيام بعملية التحليل أيضاً، وقد تمّ استخراج معامل الثّبات باستخدام معادلة هولستي ( Holsti ) للثّبات، حيث بلغ معامل الثبات عبر الزمن( 7.89 %)، وعبر الأشخاص ( 8.86 %)، وهذا المعامل مقبول لأغراض الدّراسة، وقد تمّ استخدام التّكرارات والنسب المئوية، وكشفت نتائج الدراسة عن تدنّي توافر المعايير المعاصرة للتّربية البيئية في تلك الكُتب. وفي ضَوء نتائج الدّراسة أوصى الباحث بتضمين البعد البيئي في كُتب التّربية الإسلامية للمرحلة الأساسية المتوسطة في الأردن، بإدخال معلومات ومفاهيم بيئية، أو ربط المحتوى بقضايا بيئية مناسبة.
This study aimed to Abstract Evaluation of the Islamic Education Student's Books for the Lower Basic Stage in Jordan According to the Contemporary Criteria for the Environmental Education, the study sample consisted of the same study population, the Islamic Education Textbooks of basic upper stage the Ministry of Education for the academic year 2015/2016. In order to achieve the objectives of the study, researcher developed measuring instrument, and the analysis included nine axles, and twenty-seven standard contemporary environmental Educational basic stage, has been the tool presented to the committee of judges who specialize in the curriculum, and the environment; to make sure of the sincerity, then the researcher process analysis, where was assigned to one of the teachers, who holds a master's degree in curriculum and methods of teaching Islamic education to do the analysis process, too. reliability factor has been extracted using holsti equation (Holsti) for stability, reaching reliability coefficient over time (%89.7), and through the people (%86.8) and this parameter is acceptable for the purposes of the study, frequencies, percentages were used, and the study's results revealed the low availability of contemporary standards of environmental education in those books.. In light of the findings, the researcher recommended : Including the environmental dimension in the books of Islamic education for the higher stage of basic education in Jordan, to enter information and concepts of environmental, or linking content appropriate environmental issues The lower basic stage, contemporary.
Keywords: المرحلة المتوسطة -- المناهج الدراسية -- كتب التربية الإسلامية -- التقويم التربوي -- التربية البيئية -- المعايير البيئية